Bad moms Christmas - Lucas, Jon, 1976-; Moore, Scott (Screenwriter); Todd, Suzanne; Kunis, Mila, 1983-; Bell, Kristen, 1980-; Hahn, Kathryn, 1974-; Hernandez, Jay, 1978-; Hines, Cheryl; Gallagher, Peter, 1955-; Hartley, Justin, 1977-; Baranski, Christine; Sarandon, Susan, 1946-; et al. (Universal City, CA Universal Pictures Home Entertainment, 2018)
Follows three under appreciated and over burdened women as they rebel against the challenges and expectations of the Super Bowl for moms: Christmas. If creating a more perfect holiday for their families wasn't hard enough, they have to do all of that while hosting and entertaining their own mothers.
Originally released as a motion picture in 2017.
Anamorphic wide screen (2.40:1).
Bonus features: Gag reel; additional scenes; crew music video; trailers.
Director of photography, Mitchell Amundsen ; editor, James Thomas ; music, Christopher Lennertz.
Mila Kunis, Kristen Bell, Kathryn Hahn, Jay Hernandez, Cheryl Hines, Peter Gallagher, Justin Hartley, Christine Baranski, Susan Sarandon.
MPAA rating: R; for crude sexual content and language throughout, and some drug use.
Keywords: Mothers -- Drama; Holiday stress -- Drama; Mothers and daughters -- Drama; Motherhood -- Drama; Christmas plays; Families -- Drama; Action and adventure films; Christmas films; Comedy films; Drama; Feature films; Fiction films; Video recordings for the hearing impaired